Strategi Komunikasi dalam Menampilkan Citra Anak Muda pada Program Acara Talkshow - Novita Ika Purnamasari; Noer Aisyah Rachmawati (MUKASI: Jurnal Ilmu Komunikasi, 2023)
TalkCation is a talk show program in collaboration with local television station RBTV Yogyakarta and Yogyakarta Amikom University. This program carries an educational theme wrapped in a youth style so that it can compete with other television stations. The television industry is a dynamic industry, where creativity is the most important thing to make the programs attractive. For this reason, the existence of a creative team is a division that is the key to success in generating creative ideas in creating interesting programs, especially when television is starting to lose its prestige, especially among the younger generation. This is what underlies researchers to conduct research related to the communication strategy carried out by the creative team in packaging a local TV program by presenting the image of young people as the audience. Using the concept of elements and creative space by Rusman Latief and Yustiatie Utud, and examining the application of communication strategy theory to the preparation of creative team communication strategies, researchers conducted a study using a qualitative descriptive approach. The result of this research is that the communication strategy of the TalkCation creative team apparently applies the stages of the communication strategy in the Assify and French models. In addition, the image of young people shown in the program's packaging followed by collaboration between the creative team, the media team and public relations seems to have been effective in attracting the audience's interest in watching TalkCation programs.